CONFLICT TOLERANCE OF A TEACHER: DIAGNOSIS AND DEVELOPMENT - Koryakovtseva, Olga; Yuferova, Marina; Bugaychuk, Tatiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
In today's rapidly developing society conflict tolerance is an important quality of professionals in different areas. The question of the teacher’s tolerance to conflict has not been studies well enough. The results of this research disclose relationships between indicators general adaptability and components of conflict tolerance of future teachers, which is important in the formation and development of conflict tolerance of a teacher